The migration of the Tringa Linnaeus, 1758 species at Chukh Lake, Eastern Mongolia - Enkhzaya, Turmunkh; Altangerel, Tsogtmagnai; Amarkhuu, Gungaa; Jiao, Shengwu; Oyunchimeg, Terbish; Gankhuyag, Purev-Ochir (Proceedings of the Institute of Biology, 2023)
The genus Tringa comprises 13 species worldwide, with eight species registered in Mongolia. Despite this taxonomic richness, comprehension of migration patterns and routes for Tringa species during the spring and autumn seasons in Mongolia remains unknown. This article unveils the outcomes of an intensive study conducted at Chukh Lake in eastern Mongolia spanning the years 2019 to 2021. Over the course of survey periods, we ringed a total of 277 individuals from seven species of Tringa. In the year 2019, the pinnacle of spring migration was observed from May 26th to 30th, while in 2020 the peak occurred between May 14th and May 20th. Notably, the autumn migration peak was consistently recorded between August 1st and August 4th over three years of continuous monitoring, indicating a remarkable stability in their autumn migratory patterns. Utilizing GSM-based transmitters, the trajectories of seven individuals from four Tringa species were meticulously tracked from Chukh Lake to their wintering and breeding areas during both inbound and outbound migration periods. Remarkable journeys were documented, including an adult Spotted Redshank traversing 2027.3 km from Chukh Lake to winter in Henan, China. Similarly, a Common Greenshank covered 2444 km to winter in Hunan, China. Noteworthy observations include an adult Grey-tailed Tattler, initially recorded in Arakhley Lake, Russia, eight days post-tracking, and subsequently registered in Zhouzi, China, after an elapsed period of 54 days. The extensive migratory capabilities of the adult Common Redshank were highlighted, covering 5690 km in autumn and 6000 km in spring. Чух нуураар дайран өнгөрөх хөгчүү (Tringa Linnaeus, 1758) төрлийн шувуудын нүүдэл Дэлхийд хөгчүү (Tringa) төрлийн нийт 13 зүйл, манай оронд 8 зүйл шувуу бүртгэгдсэн ба тэдгээрийн хавар, намрын нүүдлийн оргил үе тодорхойгүй, нүүдлийн замналын талаарх баримт хомс байна. Бид энэ өгүүлэлдээ Чух нуурт 2019-2021 онд гүйцэтгэсэн судалгааны үр дүнгээ орууллаа. Чух нуурт гурван жилд хөгчүүний төрлийн долоон зүйлийн 277 бодгаль шувууг барьж, бөгжилсөн. Чух нуураар дайран өнгөрч буй шувуудын хаврын нүүдлийн идэвхжил 2019 онд 5-р сарын 26-30-ны хооронд тохиосон бол 2020 онд 5-р сарын 14-20-ний хооронд байв. Намрын нүүдлийн идэвхжил гурван жилийн хугацаанд 8-р сарын 01-ээс 4-ний хооронд тохиосон харьцангуй тогтвортой байна. Бид дөрвөн зүйл хөгчүүний долоон бодгальд сансрын дамжуулагч зүүж тэдгээрийн нүүдлийн замнал, үрждэг, өвөлждөг мөн нүүдлийн үедээ бууж амардаг газруудыг тодорхойллоо. Хар хөгчүүний бие гүйцсэн бодгаль Чух нуураас 2027.3 км зам туулан Хятадын Хенан (Henan) мужид хүрч өвөлжсөн бол Үхэр хөгчүү Чух нуураас 2444 км зам туулж Хятадын Хунаньд (Hunan) хүрсэн. Буурал хөгчүүний бие гүйцсэн бодгаль дамжуулагч зүүснээс найман өдрийн дараа Оросын Арахлей (Arakhley) нууранд бүртгэгдсэн. Үүнээс хойш 54 өдрийн дараа Хятадын Жоу Зи (Zhouzi) мужид бүртгэгдсэн. Улаанхөлт хөгчүүний бие гүйцсэн бодгаль намрын нүүдэлдээ 5690 км, хаврын нүүдэлдээ 6000 км замыг туулсан. Түлхүүр үгс: нүүдлийн оргил үе, сансрын дамжуулагч, Монгол дагуур